Sketches for an aesthetics of reception based on if a winter night a traveler (2004)
One of the most significant topics in the aesthetics of reception is the bringing of the audience just to the center of the aesthetic experience. This shall be the main character of the artistic phenomenon and thus shall constitute tha axis of the triangle creator-work-spectator. The protagonism of the receiver is directly linked lo the author's death. In the New Criticism scene and in the scene of the fiction of if a  Winter Night a Traveler, the author will be pushed aside by the production of senses on the part of the receiver. On the other hand we will pick up the theoretical postulates of the aesthetics of the reception  resent in I Calvino´s novel where one of the most important ones rests on the fact that the meaning difference is not in the texts themselves but in their reception, i.e., "the meaning of the masterpieces of art is generated only in the process of their interpretation".